Systems of play : activating creative play through generative systems : an exegesis presented in partial fulfilment of the requirements for the degree of Masters of Design, Massey University, College of Creative Arts, Wellington, New Zealand - Peters, Michael (Massey University, 2023)
The visual design process can be exciting and challenging as designers strive to create innovative and impactful solutions. However, the challenge of producing original outputs within the time constraints of commercial context can lead to designers falling back on well-worn techniques, templated solutions, or imitating others’ work. This fast-tracking of the divergent ideation phase of the design process reduces the possibility for experimentation and play, resulting in safe and expected outputs. Research indicates that creative play has potential to enrich the creative process, improving divergent thinking and well-being. This project explores the potential of generative design systems to enable creative play through a series of visual design experiments using mixed methods inspired by practitioners in the generative art, music and design fields. Employing an auto-ethnographic perspective, these experiments are analysed through the lens of play theory and contextualised with insights drawn from a decade of experience working within the communication design industry. The outcome of this research demonstrates that generative systems can help enrich the divergent ideation phase through enabling creative play. Experiment results indicate that these systems can encourage focused creativity, variety and quantity, creative risk-taking and novel outputs and have great potential for application in industry.
Figures 6, 8, 14, 15, 18, 22 & 29 are reused under the NZ Copyright Act 1994 s.42 which provides for the copying of a work for purposes of criticism or review.
Keywords: 330310 Interaction and experience design